2006
DOI: 10.1209/epl/i2005-10455-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-exponential relaxation for anomalous diffusion

Abstract: We study the relaxation process in normal and anomalous diffusion regimes for systems described by a generalized Langevin equation (GLE). We demonstrate the existence of a very general correlation function which describes the relaxation phenomena. Such function is even; therefore, it cannot be an exponential or a stretched exponential. However, for a proper choice of the parameters, those functions can be reproduced within certain intervals with good precision. We also show the passage from the non-Markovian t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 37 publications
1
58
0
Order By: Relevance
“…21 from t to s , rearranging, and inverting, we arrive at the solution Cpfalse(tfalse)=3kBTkpEα,1true[kpNξnormalΓfalse(3αfalse)tαtrue], where E α,β ( x ) is the Mittag-Leffler function Eα,βfalse(xfalse)=j=0xjnormalΓfalse(β+αjfalse). In the limit α → 1, the correlation function is C p ( t ) = (3 k B T/k p ) exp [− k p t /( N ξ)], which corresponds to the behavior of the Rouse model in a Newtonian fluid [17]. However, in a viscoelastic fluid, where 0 < α < 1, the correlation function decays more slowly than an exponential, characteristically as a stretched exponential at short times and as an inverse power law at long times [21]. …”
Section: Polymer In a Viscoelastic Fluidmentioning
confidence: 99%
“…21 from t to s , rearranging, and inverting, we arrive at the solution Cpfalse(tfalse)=3kBTkpEα,1true[kpNξnormalΓfalse(3αfalse)tαtrue], where E α,β ( x ) is the Mittag-Leffler function Eα,βfalse(xfalse)=j=0xjnormalΓfalse(β+αjfalse). In the limit α → 1, the correlation function is C p ( t ) = (3 k B T/k p ) exp [− k p t /( N ξ)], which corresponds to the behavior of the Rouse model in a Newtonian fluid [17]. However, in a viscoelastic fluid, where 0 < α < 1, the correlation function decays more slowly than an exponential, characteristically as a stretched exponential at short times and as an inverse power law at long times [21]. …”
Section: Polymer In a Viscoelastic Fluidmentioning
confidence: 99%
“…where the exponent classifies the different types of diffusion: subdiffusion for 0 < < 1, normal diffusion for ¼ 1, and superdiffusion for 1 < 2; for ¼ 2 the process is called ballistic [5,[14][15][16][17]. According to Kubo's linear response theory [18], the diffusion constant is given by…”
mentioning
confidence: 99%
“…Noise of this form can be obtained either by formal methods or empirical data. Using this expression, Vainstein et al [12] have shown that ν = β for β ≤ 1 and ν = 1 for β ≥ 1 consequently ν ≤ 1, i.e. ballistic is the highest asymptotic limit for diffusion.…”
Section: Diffusion Phenomenamentioning
confidence: 99%
“…where the exponent α classifies the different types of diffusion: subdiffusion for 0 < α < 1, normal diffusion for α = 1, and superdiffusion for 1 < α ≤ 2; for α = 2 the process is called ballistic [5,7,11,12,13]. Morgado et al [11] obtained a general relationship between the Laplace transform of the memory functionΠ(z) and the diffusion exponent…”
Section: Diffusion Phenomenamentioning
confidence: 99%